Priming effect in children with Type 1 Diabetes Mellitus. Issue 1 (2nd January 2020) - Giganti, F.; Gavazzi, G.; Righi, S.; Rossi, A.; Caprilli, S.; Giovannelli, F.; Toni, S.; Rebai, M.; Viggiano, M. P.
ABSTRACT: Previous studies have evidenced cognitive difficulties across various domains in Type 1 Diabetes Mellitus (T1DM) children, but the implicit memory system has not yet been systematically explored. Taking into account that the interplay between memory and perception may be modulated by the semantic category of the stimuli and their salience, we explored explicit and implicit memory using both object and food stimuli to verify whether for T1DM children there is a feebleness in performing the function of memory as a function of the stimuli used. Eighteen T1DM children and 47 healthy children performed an explicit recognition task in which they were requested to judge whether the presented image had already been shown ("old") or not ("new") and an identification priming task in which they were asked to name new and old pictures presented at nine ascending levels of spatial filtering. Results did not reveal any differences between controls and T1DM children in the explicit memory recognition task, whereas some differences between the two groups were found in the identification priming task. In T1DM children, the priming effect was observed only for food images. The dissociation between implicit and explicit memory observed in children with diabetes seems to be modulated by the category of the stimuli, and these results underscore the relevance of taking into account this variable when exploring cognitive functions.